2011
DOI: 10.1155/2011/502191
|View full text |Cite
|
Sign up to set email alerts
|

Successful Treatment of Stent Knot in the Proximal Ureter Using Ureteroscopy and Holmium Laser

Abstract: Knotted ureteral stent is rare yet tedious complication that might represent a treatment challenge to the endourologist. Only twelve cases of knotted stent have been reported. Different management options have been reported, including simple traction, ureteroscopy, percutaneous removal, and open surgery. In this paper, we present the successful untying of the knot using ureteroscopy with holmium laser.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…This includes gentle traction, 8,13,14,16,18 ureteroscopic-assisted removal, 11,20 use of a stiff guide wire, 12,17 percutaneous removal, 9,10 open ureterotomy 15 and use of a holmium laser. 19,21,22 In four of our cases where we used holmium laser, three stents were successfully removed using this method. This method of removing knotted proximal stents was first described by Richards et al 19 and subsequently used by Karagüzel et al 21 and Nettle et al 23 We found this minimally invasive approach safe and reproducible and no complications were encountered.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…This includes gentle traction, 8,13,14,16,18 ureteroscopic-assisted removal, 11,20 use of a stiff guide wire, 12,17 percutaneous removal, 9,10 open ureterotomy 15 and use of a holmium laser. 19,21,22 In four of our cases where we used holmium laser, three stents were successfully removed using this method. This method of removing knotted proximal stents was first described by Richards et al 19 and subsequently used by Karagüzel et al 21 and Nettle et al 23 We found this minimally invasive approach safe and reproducible and no complications were encountered.…”
Section: Discussionmentioning
confidence: 87%
“…11,12,14,16,18,23 Of the 20 cases involving proximal knotting of the stent including our five cases, four studies do not completely identify what stent type was used. 8,19,20,22 Of the remaining 16 cases involving proximal stent knotting, 12 involved using multilength stents. Therefore only four of 16 cases of proximal stent knotting where stent length was identified were fixed-length stents.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A rare complication is knotting, with associated difficult removal having being reported in only 15 previous cases. [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] A wide range of methods for removal has been presented, including short-and long-term traction, ureteroscopic assisted removal, use of a stiff Amplatz type guidewire, percutaneous removal, and most recently, one case describing ablation of the knot with holmium laser. 7 We present an additional case describing our eventual choice of holmium laser ablation to remove a proximal knotted Double-J stent and a literature review of other methods previously used.…”
Section: Introductionmentioning
confidence: 99%